Assessment of the seafood safety knowledge and practices of consumers in the coastal towns of Danajon Bank, Bohol Island - Magallon, Jave P.
Consumers in Bohol have access to different types of seafood because of the various bodies of water inside and outside the province. Given the availability of seafood in the area, it is essential to determine the vulnerability of consumers from Bohol to foodborne illnesses associated with seafood consumption. This study assessed the current seafood handling knowledge and practices of consumers from the coastal towns of Bohol with jurisdiction over Danajon Bank. These coastal towns are Bien Unido, Buenavista, Clarin, Getafe, Inabanga, Pres. Carlos P. Garcia, Talibon, Tubigon, and Ubay. An online survey through Google Forms was utilized in this study to collect responses from 100 seafood consumers from the said coastal towns who are aged 18 years old and above. The responses from the survey showed various unsafe practices in seafood handling and lacking seafood safety knowledge. Half the respondents do not buy seafood last or before leaving the market. Most (31.00%) fail to store leftover cooked seafood in shallow covered containers. The majority (91.00% and 32.00%, respectively) also thaw frozen seafood under water and leave cooked seafood at room temperature. They mostly think there is only a "moderate possibility" of getting sick from eating raw seafood. Lastly, most failed to recognize Vibrio and norovirus as foodborne pathogens associated with seafood consumption. To increase public awareness of safe seafood handling and the risks associated with seafood consumption, the government can create more programs to educate the public on food safety. Furthermore, the government can also explore the greater integration of food safety education into the curriculum of Filipino students.